Static in the system : noise and the soundscape of American cinema culture - Ward, Meredith C., 1981- (California studies in music, sound, and media, 2019)
"Static in the System analyzes the relationship between American aural cultural history and cinema. Focusing specifically on the field of cinema culture--the envelope that surrounds and conditions our experience of cinema as an art form--Meredith C. Ward discusses how the aural culture of a given time period has enabled certain types of listening cultures to form. Analyzing which forms of listening have been dominant in various periods, she also discusses how noise--that commonly used but little-understood term--helps us to make sense of the ongoing conflicts underlying these moments, and where we have, historically, set the limits of 'desirable' and 'undesirable' sound"--Provided by publisher.